Polia (Polia) vesperugo Eversmann 1856 - Varga, Zoltán; Ronkay, Gábor; Nagy, Jenő; Ronkay, László (Zenodo, 2020)
Polia (Polia) vesperugo Eversmann, 1856 Polia vesperugo Eversmann, 1856, Bulletin de la Société Impériale des Naturalistes de Moscou 29 (3): 48, pl. 2, fig. 6. Type-locality: [Russia] Transbaikalia, Irkutsk. Lectotype: female, in coll. ZISP. Taxonomic notes. This species was mentioned in the earlier publications as P. conspicua (Bang-Haas, 1912). The synonymy with P. vesperugo was stated and the lectotype was designated by VARGA et al. (2017). The geographically separated population groups of the species were originally described as distinct species (Sayan Mts: P. conspicua Bang-Haas, 1912; Russian Far East, Primorye distr.: P. vasjurini Sukhareva, 1976; North Finland, Inari: P. sabmeana Mikkola, 1980). They were considered as subspecies of a Siberian tundro-alpine species by HACKER et al. (2002), based on the presumably much larger distribution of the species (KONONENKO 1990). However, the taxonomic analysis of these externally different populations requires further studies. Published as part of Varga, Zoltán, Ronkay, Gábor, Nagy, Jenő & Ronkay, László, 2020, Contribution To The Taxonomy And Phylogeny Of The Genus Polia Ochsenheimer, 1816 (Noctuidae, Noctuinae, Hadenini): Species Groups And Pairs In The Holarctic Subgenus Polia S. Str., pp. 35-67 in Acta Zoologica Academiae Scientiarum Hungaricae 66 (1) on pages 51-52, DOI:10.17109/AZH.66.1.35.2020, http://zenodo.org/record/5734753